Analisis Kerjasama Tim dan Komunikasi Terhadap Kinerja Karyawan PT. Pelindo Marine Service - Bagus Ramadhani Putra Perkasa; Nur Widyawati (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
Every company certainly has a vision and mission that it wants to achieve, therefore it definitely needs employees who can fulfill and support the company so that it can progress and develop. Therefore, teamwork and communication are needed for each individual employee to achieve the vision and mission. This research aims to determine the analysis of teamwork and communication on employee performance at PT. Pelindo Marine Services. Using the Slovin formula by taking the entire population as a sample for the possibility of small errors. The sample taken was 30 respondents, namely employees of PT. Pelindo Marine Services. The data analysis methods used are validity test, reliability test, classical assumption test, linear regression analysis, t test and f test, as well as the coefficient of determination test (R^2). The results of this research state that: 1) Teamwork has a significant and positive effect on employee performance, which means that if teamwork increases then employee performance will also increase, 2) Communication has a significant and positive effect on employee performance, which means that if teamwork increases then performance employees also increased. 3) Teamwork and communication have a simultaneous effect on employee performance, which means that if teamwork and employee communication increase, employee performance will also increase. Conversely, if teamwork and communication decreases, employee performance will decrease.